DIGITALIZATION OF PAI LEARNING IN FORMING THE RELIGIOUS CHARACTER OF STUDENTS AT THE PRIVATE ISLAMIC MTS PADANGGARUGUR - Saurmatua Siregar; Hasnil Aida (Jurnal Bilqolam Pendidikan Islam, 2026)
The digitalization of Islamic Religious Education (PAI) learning is a transformation of the learning system that utilizes digital technology to improve the effectiveness, accessibility, and quality of education. The digitalization of PAI learning brings significant transformations in various sectors of life, including Islamic education. Digitalization not only changes the method of presenting knowledge, but also opens new opportunities in the internalization of balanced Islamic values. In this case, the digitalization of Islamic education plays an important role as a means of strengthening peace education that aims to instill the values of tolerance, empathy, and social justice. The process of digitalizing Islamic education can strengthen peace education through the integration of information technology in learning activities, da'wah, and Islamic character training. Thus, it can form a religious character of students in overcoming moral crises, juvenile delinquency, and misuse of technology in students. The values of honesty, responsibility, discipline, and Islamic digital literacy are instilled in students